Dielectric Properties of ZnO-Based Nanocomposites and Their Potential Applications - Kaur, Daljeet; Bharti, Amardeep; Sharma, Tripti; Madhu, Charu (International Journal of Optics, 2021)
Energy storage devices constitute one of the research areas in recent years. Capacitors are commonly used for the storage of electrical energy. The current research is focusing on not only the improvement in energy density but also the materials which are environment friendly. Polymer composites are known to be technically essential materials owing to their wide range of applications. Enormous research has been devoted to zinc oxide- (ZnO-) based polymer nanocomposites, due to their extraordinary dielectric properties. This review article presents a detailed study of the dielectric properties of ZnO-based nanocomposites. The dielectric constant study includes the effect of transition metals and rare earth metals as a dopant in ZnO. This review gives an insight into the mechanism responsible for the variation of dielectric constant in ZnO nanocomposites due to various factors like size of nanoparticles, thickness of the thin film, operating frequency, doping concentration, and atomic number. The observations have been summarized to convey the mechanism and structural changes involved in the ZnO nanocomposites to the researchers. The deployment of biodegradable nanocomposite materials is expected to open an innovative way for their outstanding electronic applications as storage materials.